Implementation of Multi-Factor Authentication on A Vaccination Record System - TEH, YU FUNG; Ramli, Sofia Najwa (Applied Information Technology And Computer Science, 2023)
The vaccination Record System is widely used worldwide during the pandemic of COVID-19 and led to information leakage and faking of vaccine certificates. This study aims to design, develop and evaluate android-based vaccination record system with multi-factor authentication named Jom-Vaccine. At the same time, the scopes of the research focus primarily on its security mechanism by implementing multi-factor authentication such as OTP verification and fingerprint recognition. The proposed application is developed by adopting prototype modelling and using Android Studio, Firebase and Java language. The findings show that the proposed application can increase the security level by preventing unauthorized access to the application and preventing leakage of sensitive data. The study's objectives will be achieved based on the user acceptance form and test plan. Overall, the vaccination record system with multi-factor authentication can be used in a real-world scenario with further improvements.